Near infrared photoimmunotherapy in the treatment of disseminated peritoneal ovarian cancer - Sato, Kazuhide (Mol Cancer Ther, 2014)
Near infrared photoimmunotherapy (NIR-PIT) is a new cancer treatment that combines the specificity of intravenously injected antibodies for targeting tumors with the toxicity induced by photosensitizers after exposure to near infrared (NIR) light. Herein, we evaluate the efficacy of NIR-PIT in a mouse model of disseminated peritoneal ovarian cancer. In vitro and in vivo experiments were conducted with a HER2-expressing, luciferase expressing, ovarian cancer cell line (SKOV-luc). An antibody-photosensitizer conjugate (APC) consisting of trastuzumab and a phthalocyanine dye, IRDye-700DX, was synthesized (tra-IR700) and cells or tumors were exposed to near infrared (NIR) light. In vitro PIT cytotoxicity was assessed with dead staining and luciferase activity in freely growing cells and in a 3D spheroid model. In vivo NIR-PIT was performed in mice with tumors implanted in the peritoneum and in the flank and these assessed by tumor volume and/or bioluminescence. In vitro NIR-PIT-induced cytotoxicity was light dose dependent. Repeated light exposures induced complete tumor cell killing in the 3D spheroid model. In vivo the anti-tumor effects of NIR-PIT were confirmed by significant reductions in both tumor volume and luciferase activity in the flank model (NIR-PIT vs control in tumor volume changes at day 10; p=0.0001, NIR-PIT vs control in luciferase activity at day 4; p=0.0237), and the peritoneal model (NIR-PIT vs control in luciferase activity at day 7; p=0.0037). NIR-PIT provided effective cell killing in this HER2 positive model of disseminated peritoneal ovarian cancer. Thus, NIR-PIT is a promising new therapy for the treatment of disseminated peritoneal tumors.